Oxford studies in philosophy of religion: Volume 7 - Kvanvig, Jonathan L. (Oxford University Press, 2016)
'Oxford Studies in Philosophy of Religion' is an annual volume offering a regular snapshot of state-of-the-art work in this longstanding area of philosophy that has seen an explosive growth of interest over the past half century